EHealth Literacy and Caregiver Burden Among Chinese Caregivers of Older Adults With Cognitive Impairment: Does Education Matter?. (December 2021) - Wang, Kaipeng; Gao, Xiang; Sun, Fei; Bishop, Nicholas J.
EHealth literacy is a critical factor that influences caregivers' well-being. The purpose of this study is to examine the association between eHealth literacy, education, and caregiver burden among Chinese caregivers of older adults with cognitive impairment. Data came from structured interviews with 300 primary family caregiver–care recipient dyads in Wuhan, China. We used logistic regression to examine the association between eHealth literacy, education, and caregiver burden. An interaction effect between eHealth literacy and education on caregiver burden was identified. eHealth literacy was positively associated with caregiver burden among caregivers with less than a high school education, but not among those with a high school education or above. eHealth literacy is salient in the burden experienced by caregivers with low education. eHealth literacy needs to be enhanced with health information verification from health professionals and programs to support caregiving efficacy to realize its positive impact on caregivers' mental health.